2017
DOI: 10.5114/reum.2017.69776
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hospitalization and mortality of scleroderma in-patients: a thirteen-year study

Abstract: ObjectiveSystemic sclerosis (SSc) is an uncommon non-hereditary sporadic disease that increases the risk of premature death, especially in diffuse type. We determined the prevalence of SSc in the last 13 years in our rheumatologic hospitals as a referral center for southern Iranian patients, the causes of hospitalization, the average length of stay (LOS), the mortality rate, and the reason for their mortality.Material and methodsA cross-sectional study was performed in Shiraz University of Medical Sciences, Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…However, causes of acute admission changed over time, and are different from those reported in studies prior to 2010. In our cohort there was a higher percentage of hospitalizations due to infection (27%) and cardiac disease (16.5%), and not ILD as reported in other studies [ 13 , 14 , 16 ]. Tables 4 , 5 summarizes published studies on hospitalization of patients with systemic sclerosis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, causes of acute admission changed over time, and are different from those reported in studies prior to 2010. In our cohort there was a higher percentage of hospitalizations due to infection (27%) and cardiac disease (16.5%), and not ILD as reported in other studies [ 13 , 14 , 16 ]. Tables 4 , 5 summarizes published studies on hospitalization of patients with systemic sclerosis.…”
Section: Discussionsupporting
confidence: 70%
“…Piga M. et al [ 14 ] performed an annual trend analysis showing a statistically significant increase in the percentage of ILD ( p < 0.0001), PAH ( p < 0.0024), digital ulcers, and gangrene ( p = 0.0037), between the years of 2001–2012. In a study by Shenavandeh S. et al [ 16 ] including 181 patients and 446 admissions, comprising a total of 13 years of follow-up (1999–2012), the most common causes of hospitalization were DU in 39.7%, and interstitial lung disease and PH in 21.1%. Additionally, ILD and PH were the most frequent causes of mortality in 33.3% of the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 8-12% of patients with SSc will develop PH [24][25] and it is one of the leading causes of death in this condition 26 . Despite extensive efforts at the early identification of PH in SSc patients, this population continues to have PH detected at an advanced stage 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The difference between sexes has been proven by previous studies on most rheumatic diseases. In most rheumatic diseases like PMR, GCA, scleroderma, SLE, etc., female gender was a predisposing factor; one exception is gout, which was more prevalent in men [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In the group with known rheumatologic diseases, the second most prevalent cause of admission was scleroderma (5.9%), and the third was SLE (3.7%). The causes of the high rate of scleroderma admissions have been studied by the authors in a previously published study; although all age groups of patients were evaluated, it was found that uncontrolled digital ulcers, interstitial lung disease (ILD), and infections were the most common causes of hospitalization for this group of patients in the studied center (4).…”
Section: Discussionmentioning
confidence: 99%